THE LEGAL STATUS OF UNCERTIFIED LAND IN INDONESIA: CHALLENGES AND PATHWAYS TO OWNERSHIP CERTIFICATION UNDER AGRARIAN LAW - Hadrian, Endang (UNISSULA, 2024)
Every individual has the right to private property, and these rights cannot be taken arbitrarily. Before the enactment of the Basic Agrarian Law (UUPA) in Indonesia, a dualism in agrarian regulations existed, leading to various forms of land tenure. One such form is